Career adaptation in higher education: a study with non-working and working students - Soares, Joana; Taveira, Maria do Céu (Frontiers in Education, 2024)
The career construction and sociocognitive career theories were considered to test an integrative model of career adaptation in higher education. Participants were 523 Portuguese university students (non-working, n = 335, Mage = 20.64; working, n = 188, Mage = 29.05), who completed measures of social support, protean orientation, adaptability and adapting as adaptation predictors, and career certainty, academic well-being, and life satisfaction as adaptation outcomes. Multigroup path analysis results indicated a good fit of the model and invariance across groups after some changes. Although more studies are needed to explore the range and limits of the proposed model validity, our findings allow the career development literature extension while informing the practice. Career counselors might facilitate university students' adjustment by helping them expand their social network and develop their career attitudes.